Effects of plasma jet, dielectric barrier discharge, photodynamic therapy and sodium hypochlorite on infected curved root canals. Issue 3 (8th November 2017) - Ballout, Husam; Hertel, Moritz; Doehring, Jonas; Kostka, Eckehard; Hartwig, Stefan; Paris, Sebastian; Preissner, Saskia
Abstract : The aim of this investigation was to evaluate the effects of 2 different cold atmospheric plasma (CAP) sources, photodynamic therapy and sodium hypochlorite (NaOCl), on infected root canals. Therefore, 50 standardized curved human root canals were infected with Enterococcus faecalis and assigned to 5 groups—negative control (NC), plasma jet (CAP I), dielectric barrier discharge (CAP II), photodynamic therapy (PDT) and NaOCl + passive ultrasonic irrigation—for 30 s. Colony forming units (CFUs) were determined. NaOCl was significantly more effective at reducing CFUs than all test groups ( P < .0001 [Mann‐Whitney U test]) in both parts of the root canal. CFUs in PDT were significantly lower than those in CAP II ( P = .015), and those in CAP I were lower than those in CAP II ( P = .05). Among all other groups and in the apical parts, no significant differences were found ( P > .05). Abstract : To evaluate the effects of photodynamic therapy (PDT), an indirect plasma jet (CAP I) and a direct plasma (CAP II) we produced 50 standardized curved human root canals. Canals were infected with E. faecalis and incubated for 6 days. Antibacterial treatment was carried out with sodium hypochlorite (NaOCl) and ultrasonic activation, PDT, CAP I, CAP II. In the negative control group (NC) root canals were rinsed with using sterile NaCl. Samples of coronal and apical regions were obtained using peeso burs and analyzed counting colony forming units (CFU) and performing scanning elctron microscopy (SEM).